Strategi Pengembangan Usaha DNI Skincentre Renon dengan Penerapan Metode Swot dan Topsis - Firdayanti, Ni Luh; Wiranatha, Agung Suryawan; Sadyasmara, Cokorda Anom Bayu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 8 No 1 (2020): MaretDO - 10.24843/JRMA.2020.v08.i01.p08, 2020)
The development of beauty trends in Indonesia is increasing, which makes the cosmetics industry one of the promising industries. The presence of foreign brand cosmetics makes domestic products experience sales decline. The high level of competition has become one of the factors in conducting business development strategies. The objectives of this study are 1) to analyze the internal and external environmental conditions of DNI Skin Centre, and 2) to formulate strategies and set priorities for DNI Skin Centre business development strategies. This study uses the SWOT method to determine the alternative strategies used, and the TOPSIS method to rank alternative strategies. Strategies that can be applied at DNI Skin Centre Renon are to growth and build. The first alternative priority strategy chosen is to provide education to consumers about Renon's DNI Skin Center products and treatments. The second priority alternative strategy chosen is to maintain the price and quality of the product and the third priority alternative strategy is to promote the products and treatments that exist at the Renon DNI Skin Center . Keywords: Skin Centre, Business Development Strategy, SWOT, TOPSIS